Proses Islamisasi Masuknya Agama Islam di Kota Pagaralam - Wijaya, Tomy; Saputra, Dicky Jhonson; Andini, Salsabila Fitra; Hudaidah, Hudaidah; Yati, Risa Marta (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Pagaralam City, located in South Sumatra, has an area of 633.66 Km2 (63,366 Ha), the city has a strategic geographical position that makes it a link between the highlands and lowlands in South Sumatra. The people of the city are predominantly Besemah, a community known for its unique traditions and rich culture. The word Besemah comes from the words be and semah, where the prefix be signifies presence or ownership, while semah refers to the native fish of the rivers in Pagaralam City. This research uses the historical method with an analytical descriptive qualitative approach. Then, to analyze the findings, the researchers summarized information from literature, books, and internet sources. In addition, researchers also collected information through direct observation and interviews (heuristics), checked the validity of the sources obtained (verification), looked for supporting facts (interpretation), before finally compiling a narrative (historiography). The result of this research is a cleric who played an important role in the spread of Islam in Pagaralam City, namely Sheikh Nurqodim Al-Baharud, or often called Puyang Awak. He broadcasted Islam in Pagaralam in the 17th century AD or in the 1600s. The way he preached in spreading Islam in a fun way, especially with cultural arts, such as the Guritan Art work. He broadcast Islam at the foot of Mount Dempo, precisely in Pardipe Village, besides the mosque there is a tomb of Sheikh Nurqoddim Al-Baharudin which is located about 500 meters from the settlement and is sacred by the Pagaralam people. This mosque was only roofed with zinc without insulation and became the beginning of the process of spreading Islam in Pagaralam.